What's Behind the Inequality We Measure? An Investigation Using Latin American Data - Miguel Székely; Marianne Hilgert (Luxembourg Income Study (LIS), 1999)
The use of income distribution indicators in the economics literature has increased considerably in recent years. This work relies on household surveys from 18 LAC countries to take a step back from the use of these indicators, and explore what's behind the numbers, and what information they convey. We find: a) that the way countries rank according to inequality measured in a conventional way is to a large extent an illusion created by differences in characteristics of the data and on the particular ways in which the data is treated; b) Our ideas about the effect of inequality on economic growth are also driven by quality and coverage differences in household surveys and by the way in which the data is treated; c) Standard household surveys in LAC are unable to capture the incomes of the richest sectors of society; so, the inequality we are able to measure is most likely a gross underestimation. Our main conclusion is that there is an important story behind each number. This story influences our judgment about how unequal countries are and about the relation between inequality and other development indicators, but it is seldom told or known. Perhaps other statistics commonly used in economics also have their own interesting story, and it might be worth trying to find out what it is.
Keywords: 330; Einkommensverteilung; Wirtschaftswachstum; Privater Haushalt; Lateinamerika; Datenerhebung